UJI EFEKTIVITAS FUNGISIDA KIMIA TERHADAP JAMUR PATOGEN Fusarium sp. SECARA IN VITRO - Cleoraissa Insyira; Bayo Alhusaeri Siregar; Moralita Chatri (Universitas Cokroaminoto Palopo, 2026)
Fusarium sp. is a pathogenic fungus causing wilt disease in Acacia crassicarpa nurseries and reducing seedling quality in industrial forest plantations. The control of this disease is generally done with chemical (synthetic) fungicides, but the most effective one is not yet known. This study aimed to evaluate the effectiveness of several chemical fungicides against Fusarium sp. growth in vitro. The study was conducted from February to June 2025 at the Plant Protection Department (PPD) Laboratory, R&D Division of PT. Arara Abadi using a Completely Randomized Design with four treatments: control, Octave (prochloraz–manganese chloride complex), Besromil (metalaxyl), and Odeon (chlorothalonil), with three replications. The observed parameter was the percentage of fungal growth inhibition. Data were analyzed using ANOVA followed by Duncan’s test at a 5% significance level. The results showed that Octave exhibited the highest inhibitory effect with 100% inhibition and was significantly different from other treatments. Besromil and Odeon showed low inhibition and were not significantly different from the control. Therefore, prochloraz–manganese chloride complex was the most effective fungicide in inhibiting Fusarium sp. growth in vitro.